Transient receptor potential channels in the context of nociception and pain: recent insights into TRPM3 properties and function - Behrendt, Marc (Biological chemistry, 2019)
Potential harmful stimuli like heat, mechanical pressure or chemicals are detected by specialized cutaneous nerve fiber endings of nociceptor neurons in a process called nociception. Acute stimulation results in immediate protective reflexes and pain sensation as a normal, physiological behavior. However, ongoing (chronic) pain is a severe pathophysiological condition with diverse pathogeneses that is clinically challenging because of limited therapeutic options. Therefore, an urgent need exists for new potent and specific analgesics without afflicting adverse effects. Recently, TRPM3, a member of the superfamily of transient receptor potential (TRP) ion channels, has been shown to be expressed in nociceptors and to be involved in the detection of noxious heat (acute pain) as well as inflammatory hyperalgesia (acute and chronic pain). Current results in TRPM3 research indicate that this ion channel might not only be part of yet unraveled mechanisms underlying chronic pain but also has the potential to become a clinically relevant pharmacological target of future analgesic strategies. The aim of this review is to summarize and present the basic features of TRPM3 proteins and channels, to highlight recent findings and developments and to provide an outlook on emerging directions of TRPM3 research in the field of chronic pain.